1997
DOI: 10.1128/iai.65.1.257-260.1997
|View full text |Cite
|
Sign up to set email alerts
|

Role of tumor necrosis factor alpha in pathogenesis of pneumococcal pneumonia in mice

Abstract: The production and role of tumor necrosis factor alpha (TNF-␣) in pneumococcal pneumonia were investigated in a mouse pneumonia model. When approximately 10 6 CFU of Streptococcus pneumoniae TUM19 were used to inoculate CBA/J mice intranasally, TNF-␣ levels in the lungs and serum began to increase from 1 and 3 days after infection, respectively, concomitantly with the increase in bacterial counts in the lungs. Anti-TNF-␣ antibody accelerated bacterial proliferation in the blood and the death of the mice. Altho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
44
0
2

Year Published

1999
1999
2012
2012

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 156 publications
(54 citation statements)
references
References 19 publications
8
44
0
2
Order By: Relevance
“…TNF-a is thought to play a major role in PMN recruitment [34,35]. However, similar to earlier reports, including one in a murine model of acute pulmonary PA infection [10,16,24], we found a dissociation between PMN numbers and TNF-a levels produced by alveolar macrophages in susceptible C57Bl/6 mice following PA stimulation in vitro.…”
Section: Discussionsupporting
confidence: 88%
“…TNF-a is thought to play a major role in PMN recruitment [34,35]. However, similar to earlier reports, including one in a murine model of acute pulmonary PA infection [10,16,24], we found a dissociation between PMN numbers and TNF-a levels produced by alveolar macrophages in susceptible C57Bl/6 mice following PA stimulation in vitro.…”
Section: Discussionsupporting
confidence: 88%
“…In addition, TNF- § potentiates their killing activities against microbial pathogens [45][46][47]. Many investigators have indicated the important role of these molecules in host protection against extracellular bacteria [6,7,[9][10][11]. In the present study, exacerbated infection by S. pneumoniae in V § 14 + NKT cell-deficient mice correlated well with reduced production of TNF- § and MIP-2 and hampered recruitment of neutrophils in the infected organ.…”
Section: Discussionsupporting
confidence: 59%
“…Pneumonia caused by infectious pathogens is characterized by massive accumulation of neutrophils in the alveolar spaces. Exacerbated pneumonia is observed under conditions of suppression of the CXC chemokine receptor CXCR2 and its ligands, such as macrophage inflammatory protein (MIP)-2 and lungkine [5][6][7][8], and pro-inflammatory cytokines, TNF- § , IL-1 g and IL-6 [9][10][11][12][13], and is also associated with impaired recruitment of these inflammatory leukocytes to the site of infection [5-8, 11, 12]. On the other hand, there have been few reports regarding the role of other innate immune cells in the host defense against these bacteria.…”
Section: Introductionmentioning
confidence: 99%
“…Pneumonia is associated with local production of cytokines and chemokines. Locally produced TNF prevents outgrowth of bacteria in lungs, thereby playing a protective role in experimental pneumonia with Streptococcus pneumoniae [12,33], Klebsiella pneumoniae [11] and Legionella pneumophila [34]. Like TNF, IL-6 plays an important role in host defense in pneumococcal pneumonia [12], as do chemokines in K. pneumoniae pneumonia [25] and in P. aeruginosa infection [35].…”
Section: Discussionmentioning
confidence: 99%